2020
DOI: 10.1177/1468794120904873
|View full text |Cite
|
Sign up to set email alerts
|

Ethnography of young people in confinement: on subjectivity, positionality and situated ethics in closed space

Abstract: This article explores the strengths and limitations of doing ethnographic research with young people in confinement. The article draws on two studies from Scotland and Denmark, and reflects on critical issues such as getting access, obtaining informed and voluntary consent, emotional challenges, safety, positionality and situated ethics. While a substantial body of literature addresses the methodological challenges of doing ethnographic research in prisons, the literature on doing qualitative research with you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…I tried to take some actions, like informing their PE teacher, but it pains me that I could only provide limited assistance. Although subjective attachments in ethnographic fieldwork may contribute to researcher bias, being affectively immersed in the boys’ lifeworlds also made me sensitive to—indeed painfully aware of—the vulnerabilities, desperation, and desires for recognition experienced by youth in confinement (see Henriksen and Schliehe 2020).…”
Section: Method: Ethnography At Two All-male Detention Homesmentioning
confidence: 99%
“…I tried to take some actions, like informing their PE teacher, but it pains me that I could only provide limited assistance. Although subjective attachments in ethnographic fieldwork may contribute to researcher bias, being affectively immersed in the boys’ lifeworlds also made me sensitive to—indeed painfully aware of—the vulnerabilities, desperation, and desires for recognition experienced by youth in confinement (see Henriksen and Schliehe 2020).…”
Section: Method: Ethnography At Two All-male Detention Homesmentioning
confidence: 99%
“…This emotional context can be even more acute when working with vulnerable and marginalised communities, where pain creates layers of intensity and ‘affective immersion’ (Henriksen and Schliehe, 2020: 842; Nelson, 2020; Federman et al, 2016). This context requires researchers to be highly present and empathic, ‘to pick up on slight changes in tonality, bodily unrest, (in) assertive voices, the materiality of the room, sounds, disruptions’ (Henriksen and Schliehe, 2020: 842). (Adeagbo, 2021: 191), in her work with HIV positive young mothers in South Africa, found that interviewing those who have suffered ‘creates a context that is precarious and complicated’.…”
Section: What To Do About How We Feelmentioning
confidence: 99%
“…In such painful contexts, ‘we are inevitably touching nerves, stirring anxieties, and are drawn into emotional force fields with unpredictable effects’ (Brankamp, 2021: 6). Emotionally engaged research can weave together ‘personal accounts of violence within wider analyses of power and privilege’ (Zonjić, 2021: 543), taking note of the systemic ways in which histories are inscribed in institutions that generate pain, be they refugee camps (Hagan, 2021), adoption agencies (Collings et al, 2021), mission boarding schools (Charbonneau-Dahlen et al, 2016) or criminal justice systems (Henriksen and Schliehe, 2020). It can allow space for reflection on ‘nuances of care’ (Hammoud-Beckett, 2021) and how emotions impact on the capacity to develop trusting and ethical encounters in these institutions and within the research process itself.…”
Section: What To Do About How We Feelmentioning
confidence: 99%
See 1 more Smart Citation
“…The article identifies various subjective experiences of time being 'slow' or even 'dead' when young people are kept in isolation or are waiting for their stay to be terminated, and how they actively engage in 'making time' to gain some control of their time in confinement. Especially in the UK and USA, researchers' access to closed institutions is getting increasingly difficult due to ethics boards restricting particularly qualitative and ethnographic research inside closed spaces (Henriksen & Schliehe, 2020;Myers, 2015). However, youth perspectives are vital for improving the support provided for young people in vulnerable positions, particularly interventions that include confinement or restrictive measures.…”
Section: Confinement In Locked Institutionsmentioning
confidence: 99%